Pengaruh Harga Jual, Biaya Operasional dan Pendapatan terhadap Laba Usaha - Puji Indah Rahayu; Indah Dewi Mulyani; Hendri Sucipto; Andi Yulianto; Nur Afridah (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to determine the effect of selling price, operating costs, and income on traders' business profits at the Bulakamba Traditional Market, both partially and simultaneously. The research method used is a quantitative approach with data collection techniques through questionnaires. The sample consisted of 177 respondents, determined using the Slovin formula from a total population of 318 traders. The results show that partially, selling price has a positive and significant effect on business profit, operating costs have a positive and significant effect on business profit, and income also has a positive and significant effect on business profit. Simultaneously, selling price, operating costs, and income significantly affect the business profit of the traders.